1980
DOI: 10.1017/s0031182000000482
|View full text |Cite
|
Sign up to set email alerts
|

Acid phosphatase activity demonstrated in the nematodes,Dirofilaria immitisandAngiostrongylus cantonensiswith special reference to the characters and distribution

Abstract: SummaryAcid phosphatase activity was demonstrated in the intact blood nematodes, Dirofilaria immitis and Angiostrongylus cantonensis. Biochemical studies on acid phosphatase, using intact females and whole worm, body-wall and visceral homogenates were undertaken to clarify the characteristics and the distribution of the enzyme. In D. immitis, high acid phosphatase activity was observed at pH 3·8–5·8 and in A. cantonensis, at pH 4·5–6·0. Molybdate, fluoride, copper and zinc ions and L(+)-tartrate were effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…However, it was higher than the DSP reported from Vaccinia virus (43 kDa) and from humans (20 and 21 kDa) (Guan et al 1991; Hood et al 2002). Purified enzyme was most active at pH 4·8 which is in accordance with the usual pH range 3·8 to 6·0 of parasitic helminth acid phosphatases (Maki and Yanagisawa, 1980; Fetterer and Rhoads, 1980). A marked difference has been reported in the case of the human enzyme where the pH range is 6·0 to 7·0 (Hood et al 2002).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…However, it was higher than the DSP reported from Vaccinia virus (43 kDa) and from humans (20 and 21 kDa) (Guan et al 1991; Hood et al 2002). Purified enzyme was most active at pH 4·8 which is in accordance with the usual pH range 3·8 to 6·0 of parasitic helminth acid phosphatases (Maki and Yanagisawa, 1980; Fetterer and Rhoads, 1980). A marked difference has been reported in the case of the human enzyme where the pH range is 6·0 to 7·0 (Hood et al 2002).…”
Section: Discussionsupporting
confidence: 76%
“…The Km value of S. cervi DSP obtained with pNPP, phospho-L-tyrosine and phospho-L-serine was very high when compared with other parasitic PTPs for respective substrates. In the case of filarial parasites preliminary kinetic studies were performed in D. immitis using β-glycerophosphate as substrate in crude extract that showed a relatively high Km value of 32 m M (Maki and Yanagisawa, 1980). The affinity of this phosphatase towards ADP and fructose-6-phosphate suggested that it might be playing an essential role in providing nutrition and energy metabolism as described earlier by Remaley et al (1985).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding protein digestion, significant protease activity has been observed in the subcutaneous tissue and, to a lesser extent, in the intestine and other anatomical sites, such as the testes, germ cells, uterine wall, and fertilized eggs of adult worms (249,456). These findings suggest that protease activity is related not only to nutrition but also to other processes, such as spermatogenesis in males and the production of microfilariae in females (373).…”
Section: Energy Generation and Molting In Dirofilaria Speciesmentioning
confidence: 99%
“…We assessed two viability markers, Alamar Blue ® , an indicator for metabolic cell function (Räz et al 1997) and the MTT reduction assay, which is based on a colourimetric reaction involving pyridine nucleotides cofactors (Berridge and Tan, 1993;Mosmann, 1983). In addition, we measured acid phosphatase, which is secreted in large amounts by several nematode species in feeding stages, possibly to promote extracorporeal digestion and tissue penetration (Maki and Yanagisawa, 1980;MartinezGrueiro, 2002) and which is a good indicator of the worms' fitness. We also evaluated the feeding inhibition assay (Hawdon and Schad, 1990;Kopp et al 2008), and two fairly new technologies, namely isothermal calorimetry (Braissant et al 2010) and the xCELLigence System (Roche Inc.) (Smout et al 2010).…”
mentioning
confidence: 99%